The Mediation Existence and Opportunities of State Administrative Court in Supreme Court Regulation - Maliki, Ibnu Akbar; Saputra, Nugraha Adi; Putra, Alamsyah Nurrahmad (Universitas Islam Negeri Raden Intan Lampung, 2024)
The implementation of mediation in the Indonesian judiciary is regulated in Supreme Court Regulation (PERMA) No. 1 of 2016 on Mediation Procedures in Courts. However, the PERMA only regulates the practice of mediation in District Courts and Religious Courts, not in the State Administrative Court. Nevertheless, the PERMA allows the State Administrative Court to conduct mediation by the provisions of the legislation. However, practical guidelines governing mediation at the State Administrative Court are not detailed. In practice, this legal vacuum has led to a lack of optimisation of mediation as an instrument of dispute resolution at the State Administrative Court. The research aims to analyse the extent of the opportunities provided by the Supreme Court in PERMA No. 1 of 2016 to implement mediation procedures at the State Administrative Court. This research is normative juridical and analytical descriptive conducted by literature review. The data was collected using the documentation technique to be analysed using the normative analysis method. The analysis indicated no specific rules regarding the implementation of mediation at the State Administrative Courts. Still, the opportunity is wide open when viewed from the type of case, which is generally included in the civil case type. Furthermore, then PERMA is not the only absolute legal basis for the implementation of mediation at the State Administrative Court, as confirmed in Article 130 HIR and Article 154 RBg. The PERMA only fills the legal vacuum related to mediation procedures not explained in the previous regulations. Therefore, it is necessary to reform the law related to mediation at the State Administrative Court to achieve a court with integrity, speed, simplicity and low cost.